Eğitsel Açıdan Batı Trakya Çocuk Hikâyelerine Bir Bakış / An Overview of the Western Thrace Children’s Stories From an Educational Perspective - Yeniasır, Mustafa (Journal of History Culture and Art Research, 2018)
Abstract The literature plays a significant role in the development and education of children. The children’s literature is the literature created by considering the developmental characteristics of children and a number of spiritual needs. The stories have a wide coverage among the children’s literature works showing a rapid development in the last forty years in our country. The stories play a significant role in the education of the children. The relationship between the story and child always leads us to the good, beautiful and right things. Therefore, we should choose the literature works according to the age group of the children by placing the necessary importance on stories in education. The Western Thracian Turks placed importance on the literature for the healthy development of the children in spite of all the impossibilities and attempted to create literature works for children’s worlds of emotion and thought. The Western Thracian writers contributed to the development of their minds by enriching their imaginary worlds in stories they have written for the children. Öz Çocukların gelişim ve eğitiminde edebiyatın çok önemli bir rolü vardır. Çocuk edebiyatı, çocukların gelişim özellikleri ve birtakım ruhsal ihtiyaçları göz önünde bulundurularak oluşturulan edebiyattır. Ülkemizde özellikle son kırk yılda hızlı bir gelişme gösteren çocuk edebiyatı ürünleri içerisinde hikâyeler geniş bir yer tutmaktadır. Çocuk eğitiminde hikâyelerin çok önemli bir yeri vardır. Çocuk ile hikâye arasındaki ilişki çocuğu her zaman iyiye, güzele ve doğruya götürür. Bundan dolayı eğitimde hikâyelere gereken önemi vererek, çocukların yaş grubuna uygun eserleri titizlikle seçmeliyiz. Batı Trakya Türkleri de bütün imkânsızlıklara rağmen çocukların sağlıklı gelişimi için edebiyata önem vermişler, onların duygu ve düşünce dünyasına yönelik eserler ortaya koymaya çalışmışlardır. Batı Trakyalı sanatçılar, çocuklara yönelik olarak yazmış olduğu hikâyelerde onların hayal dünyalarını zenginleştirerek düşüncelerinin gelişmesine katkı sağlamışlardır.